Science and technology policy in Greece: Policy initiatives for R&D cooperation - Ioanna Kastelli (Fondazione Eni Enrico Mattei (FEEM), 2000)
The introduction of new elements in the Greek Science and Technology policy has not been followed to the same extent by an explicit concern for the promotion of R&D co-operation. National policy in that respect has been shaped to a large extent by the European Commission's policy initiatives. Although the EU Framework Programmes and the European Support Framework I&II played an important role in setting favourable conditions for the development of R&D co-operation, it would be unrealistic to expect that they could alone influence the attitude of the Greek industrial system towards this type of co-operation. National initiatives in the field of S&T policy have followed the general orientations of the EU policy but until now have failed to establish an authentic set of coherent actions aiming at strengthening interactive processes and establishing intense linkages among economic actors. It is argued that there is no independent growing interest for the promotion of R&D co-operation, neither from the policy makers side nor from the side of the private economic actors. No significant changes in competition and IPR rules have been introduced to promote R&D co-operation.
Keywords: L52; O38; O34; L49; O31; 330; S&T policy; R&D co-operation; Greece; Forschungs- und Technologiepolitik; Forschungskooperation; Immaterialgüterrechte; Griechenland